Non-redundant roles of the CCR1 and CCR2 chemokine axes in monocyte recruitment during lung metastasis - Alessia G. Liner; Merel van Gogh; Marko Roblek; Matthias Heikenwalder; Lubor Borsig (Neoplasia: An International Journal for Oncology Research)
Monocytes and monocyte-derived macrophages facilitate cancer progression and metastasis. Inflammatory monocytes expressing CCR2 are actively recruited to metastatic lungs, where they promote tumor cell extravasation, metastatic outgrowth, and an immunosuppressive environment. The role of CCR1 in this process has remained unclear. We used Ccr1- and Ccr2-deficient mice and two different tumor cells lines, MC38 and LLC1 with and without Ccl2-deficiency in vitro and in vivo. The recruitment of both Ccr1- and Ccr2-deficient monocytes towards the Ccl2 chemokine was significantly impaired, while no substantial recruitment was observed towards Ccl5 in vitro. MC38 and LLC1 Ccl2-deficient tumor cells showed reduced lung metastasis in both Ccr1- and Ccr2-deficient mice when compared to wild-type mice. We detected reduced numbers of macrophages and myeloid cells in both chemokine receptor-deficient mice. Lung metastasis in both Ccr1- and Ccr2-deficient mice could be rescued to the same levels as in wild-type mice by an adoptive transfer of Ccr2-deficient but not Ccr1-deficient monocytic cells. Accumulation of Ccr1-deficient monocytes in the lungs was severely impaired upon intravenous monocyte injection, indicating the importance of this axis in cell recruitment. Moreover, the efficient recruitment of adoptive transferred Ccr2-deficient monocytes to the lungs and the restoration of lung metastasis suggests an involvement of an additional, Ccr2-independent chemokine pathway. This data defines the non-redundant functions of the Ccr1- and Ccr2-chemokine axes in monocyte recruitment and macrophage presence during lung metastasis. While Ccr2 is essential for the release of monocytes from the bone marrow, Ccr1 is primarily responsible for monocyte presence at metastatic sites.